Tribological behavior and characterization analysis of modified nano-CeO2 filled oily diatomite/PVDF composites. (February 2019) - Su, Chang; Wang, Huaiyuan; Li, Meiling; Qu, Yongquan; Zhu, Yanji
Abstract: By chemical modification and melt blending, lubricating oil containing two different morphologies of modified nano-CeO2 (MN-CeO2 ) was injected into modified diatomite (M-DE) to investigate diverse impacts on the tribological properties and hardness of MN-CeO2 /30 wt% oily diatomite (O-DE)/polyvinylidene fluoride (PVDF) composites. Compared with the O-DE/PVDF composites, the friction coefficient and wear rate of 0.5 wt% modified porous rod nano-CeO2 (MPRN)/O-DE/PVDF composites were reduced by 30.4% and 82.3%, respectively. The enhanced wear resistance was principally attributed to MN-CeO2 and lubricating oil stored in the porous structure of O-DE, while the MN-CeO2 directly blended in PVDF matrix could improve the crystallinity and shore hardness of the composites. Furthermore, the relevant bionic self-lubricating mechanisms and crystallization behaviors were also revealed in the paper. Highlights: Nano-CeO2 and purified diatomite were successfully modified by stearic acid. MN-CeO2 directly blended in PVDF matrix improved the crystallinity and shore hardness of composites. The friction coefficient and wear rate of 0.5wt%MPRN-CeO2 /O-DE/PVDF composites were reduced by 30.4% and 82.3%.